Nature Monitoring Device - Nurulhuda binti Che’Anawa; Muhammad Rifqi Iman Bin Mohd Nizam; Aisya Zahra Binti Mohd Shahrizan; Kasih Nuraqilah Zahraa’ Binti Mohammad Riduwan; Nur Harith Fikry Bin Mohd Hesabery (Kolej Genius Insan, USIM, 2024)
E-Proceedings 3rd Insan Junior Researchers International Conference 2022 (iJURECON 2022) : "STREAM for a better future”/Editors: Rahayu Ahmad, Muhammad Azan Tamar Jaya, Ahmad Fuad Mohamad Amin, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan. 21-23rd October 2022 (Virtual Conference) Organized By : Kolej Genius Insan,USIM